Prescription pattern of antibiotic and analgesic in endodontic treatment in Kuwaiti population: A self-administered Survey - Manal J Al-Maslamani; Faraj A Sedeqi; Alex J Moule (Wolters Kluwer Medknow Publications, 2014)
Introduction: Surgical and non-surgical endodontic treatment of involved teeth can necessitate prescription of analgesics and antimicrobials. The literature suggests confusion amongst practitioners regarding the need for adjunctive medication, mainly during non-surgical endodontic treatment, often leading to over-prescription. Aim: The aim of this study was to determine the current clinical practice of dentists participated in this study with respect to antibiotic and analgesic prescription patterns in their endodontic treatment management in Kuwait. Materials and Methods: Prescription patterns for antibiotics and analgesics were analyzed based on the responses to self-administered questionnaire (n = 169). Information was collected based on different clinical endodontic diagnostic scenarios. Statistical analysis was performed with SPSS software version 17.0 to determine relationships between prescription patterns, age, gender, and dental qualification (specialists and general dentists). Results: Ninety-two percent of dentists prescribed analgesics for the management of endodontic pain. While 16% prescribed antibiotics for severe dental pain; 62% prescribed antibiotics for acute apical abscesses. Significantly more male dentists prescribed antibiotics for dental pain than female dentists. No significant difference was found between general dental practitioners' and specialists' attitude toward drug prescriptions. Amoxicillin and ibuprofen were the most commonly prescribed medications. Conclusion: While the majority of dentists appeared to prescribe antibiotics and analgesics appropriately, some did not. This research confirmed previous studies and established a need for imparting information of evidence-based prescriptions protocols for the dentists surveyed in this study in Kuwait.